THE USE OF ENGLISH SUBTITLE IN MOVIE TO IMPROVE STUDENTS’ VOCABULARY: AN EXPERIMENTAL STUDY IN GRADE IX OF SMPN 1 GUNUNGSARI ACADEMIC YEAR 2015/2016 - Rosmia Citra Lestari (Postgraduate School, Universitas Nusa Cendana, 2018)
This study aimed to know whether using English subtitle in watching is effective or not in increasing students’ vocabulary in grade IX SMPN 1 Gunungsari Academic Year 2015/2016. This study is an experimental study. The population of this study is students in grade IX consisting of 308 students. By using purposive sampling technique, class D was selected as experimental group with 31 students and class E was selected as control group with 31 students. Both groups were given pre-test, treatment and post-test. Pre-test and post-test consisted of 20 questions, 10 questions of matching words and 10 questions of fill in the blank with kind of reading text. The type of test related to the teaching material in grade IX was narrative text because the movie was folktale movie. Assessing students’ attitude was needed in related of K-13 curriculum because the school was already used K-13 curriculum. The data was analyzed quantitatively using t-test. The result of t-test was 3.25 with t-table at 0.005 = 2.66028 and t-table at 0.001 = 3.23171 it means that t-test is higher than the t-table and therefore the use of English subtitle was effective in increasing students’ vocabulary.